Molecular Epidemiology of Dengue Viruses in Lao People’s Democratic Republic, 2020–2023 - Cécile Troupin; Kedkeo Intavong; Somphavanh Somlor; Souksakhone Viengphouthong; Sitsana Keosenhom; Thep Aksone Chindavong; Phaithong Bounmany; Longthor Vachouaxiong; Thonglakhone Xaybounsou; Chittaphone Vanhnollat; Phonepadith Khattignavong; Darouny Phonekeo; et al. (Microorganisms)
Dengue fever is a widespread mosquito-borne viral disease caused by infections with dengue virus (DENV). Since its initial detection in 1979, the disease has posed a significant public health threat to the Lao People’s Democratic Republic (Lao PDR). Surveillance is crucial for understanding the circulation of DENV in endemic regions and identifying potential hot spots with higher-than-expected case numbers of dengue fever. In this study, we present the results from our surveillance activities in the Lao PDR spanning 2020–2023. While quarantine restrictions from the COVID-19 pandemic posed substantial disruptions to performing DENV surveillance, over 8800 samples were tested during this period, with a positive rate of close to 60%. Cases were reported from all three regions (northern, Central, and southern) of the Lao PDR. Three circulating serotypes (DENV-1, DENV-2, and DENV-4) were detected, with DENV-1 dominant in 2021 and 2022, while DENV-2 was dominant in 2020 and 2023. Phylogenetic analyses suggest that the genotypes of DENV-1, DENV-2, and DENV-4 were closely related to corresponding isolates from neighboring countries. These findings provide an update on the nature of DENV cases detected in the Lao PDR and underscore the critical importance of sustaining a robust surveillance network to track infections.